2020
DOI: 10.1101/2020.03.30.016360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ActuAtor, a molecular tool for generating force in living cells: Controlled deformation of intracellular structures

Abstract: SummaryMechanical force underlies fundamental cell functions such as division, migration and differentiation. While physical probes and devices revealed cellular mechano-responses, how force is translated inside cells to exert output functions remains largely unknown, due to the limited techniques to manipulate force intracellularly. By engineering an ActA protein, an actin nucleation promoting factor derived from Listeria monocytogenes, and implementing this in protein dimerization paradigms, we developed a m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…for centrosomes during mitotic exit [72]. To further investigate how condensates are deformed by internal forces, a novel tool called 'ActuAtor' can help, which triggers localized actin polymerization in cells in response to chemical or optical stimuli [97]. Actin localized to stress granule proteins polymerizes within these stress granules and disperses the anchor proteins of the 'ActuAtor'.…”
Section: Cytoskeletal Forces Can Deform and Rupture Condensatesmentioning
confidence: 99%
“…for centrosomes during mitotic exit [72]. To further investigate how condensates are deformed by internal forces, a novel tool called 'ActuAtor' can help, which triggers localized actin polymerization in cells in response to chemical or optical stimuli [97]. Actin localized to stress granule proteins polymerizes within these stress granules and disperses the anchor proteins of the 'ActuAtor'.…”
Section: Cytoskeletal Forces Can Deform and Rupture Condensatesmentioning
confidence: 99%
“…1b) to produce the functional iCMM effector. Similar to ActuAtor, a codon-optimized ActA functionally homologous to mActZ-FY 24 , cytosolic mActZ-FY recruitment to mitochondria by rapamycin treatment obviously transformed mitochondrial morphology to small, dot-like structures of almost equal size, in cells expressing mActZ-FY and Tom20-CR (Fig. 1e, h, and k, Supplementary movie 4).…”
Section: Resultsmentioning
confidence: 96%
“…1b). Although YF has been used as a control effector in various experimental settings 23,24 , we found that once the diffusive YF was substantially translocated to the outer surfaces of mitochondria, which was circumscribed by anchor proteins—which consisted of mitochondrial targeting sequences derived from Tom20, enhanced cyan fluorescent protein (ECFP), and FRB (termed Tom20-CR)—mitochondrial morphology changed from a basal reticular thread-like structure to large punctate structures (Fig. 1c, Supplementary movie 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations